2021
DOI: 10.3390/s21165476
|View full text |Cite
|
Sign up to set email alerts
|

SFA-MDEN: Semantic-Feature-Aided Monocular Depth Estimation Network Using Dual Branches

Abstract: Monocular depth estimation based on unsupervised learning has attracted great attention due to the rising demand for lightweight monocular vision sensors. Inspired by multi-task learning, semantic information has been used to improve the monocular depth estimation models. However, multi-task learning is still limited by multi-type annotations. As far as we know, there are scarcely any large public datasets that provide all the necessary information. Therefore, we propose a novel network architecture Semantic-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Currently, most of the work related to improving edge depth requires the introduction of an additional network, e.g., semantic segmentation [10][11][12], edge map detection networks [13][14][15], or optical flow [16]. We found that research on uncertainty, which has only recently entered the limelight, can also improve the quality of edge depth and without learning other complex networks.…”
Section: Introductionmentioning
confidence: 92%
“…Currently, most of the work related to improving edge depth requires the introduction of an additional network, e.g., semantic segmentation [10][11][12], edge map detection networks [13][14][15], or optical flow [16]. We found that research on uncertainty, which has only recently entered the limelight, can also improve the quality of edge depth and without learning other complex networks.…”
Section: Introductionmentioning
confidence: 92%